Examining Factors Influencing Pre-Service EFL Teachers’ Motivation to Develop Their English Language Literacies - Rudha Widagsa; Dery Tria Agustin; Pramugara Robby Yana; Rizkyana Wulandari (Universitas Sarjanawiyata Tamansiswa, 2026)
Abstract: English language literacy is essential for pre-service English teachers, as it shapes their academic performance, professional identity, and future classroom practices. However, many pre-service teachers in Indonesia continue to encounter challenges in developing strong English literacy skills due to motivational, contextual, and experiential constraints. Guided by Self-Determination Theory, which emphasizes the psychological needs of autonomy, competence, and relatedness, this study examined the factors influencing pre-service EFL teachers’ motivation to develop their English literacies and how these factors shape their learning trajectories. Employing a qualitative case study design, data were collected through semi-structured interviews and document analysis with two pre-service teachers enrolled in an English Education program in Yogyakarta. The findings reveal six key motivational factors: relatedness through social and environmental support, intrinsic motivation through interest in English, autonomy supported by digital technology and learning preferences, extrinsic motivation and goal orientation, and competence development through teaching experience. These factors interact to influence how pre-service teachers engage with literacy practices and internalize motivation for long-term development. The study highlights the central role of fulfilling psychological needs in sustaining literacy motivation and points out the importance of supportive learning environments, digital literacy integration, and meaningful teaching opportunities. Implications for teacher education programs include designing motivation-enhancing practices that foster positive attitudes and improve English literacy outcomes among future teachers.